Pengaruh Media Leaflet dan Film Terhadap Pengetahuan Tentang Kanker Serviks dan Partisipasi Wanita dalam Deteksi Dini Kanker Serviks di Kampung Darek Kecamatan Padangsidempuan Selatan Tahun 2015 - Ayu Ulfah Nur Lubis; Erna Mutiara; Taufik Ashar (Poltekkes Kemenkes Medan, 2017)
Cervical cancer is a health problem which spreads among the countries throughout the world including Indonesia. It has the highest rank in diseases suffered by women in the developing countries. The data from Indonesian Cancer Foundation (2013) revealed that around 500,000 women were diagnosed as being suffered from cervical cancer each year and more than 250,000 of them died. The objective of the research was to find out the influence of the media of leaflets and movie on the knowledge of cervical cancer and women’s participation in early detection of cervical cancer. The research used quasi experiment design with non-equivalent control group. The population was 116 women 18 years old above, had been married, and lived at Darek Village, Padangsidempuan Selatan Subdistrict, Padangsidempuan City. The samples consisted of three groups with 30 respondents in each group, taken by using purposive sampling technique. The analyzed by using paired t-test, Wilcoxon, One Way Anova and Kruskal Wallis test. The result of the research showed that there was the difference in the change of knowledge about cervical cancer after health education had been given using the media of leaflets and films (p = 0.028). It is suggested that the health office in Padangsidempuan Selatan subdistrict to give health education about early detection program of cervical cancer by using leaflets and movie media that is more interesting so the community interest in increasing their knowledge and participation in detecting cervical cancer.